Geodatabase and Health Risk Assessment of Avenue Trees on Selected Roads in a Tertiary Institution in Ibadan, Nigeria (2024)
Campuses of Nigerian universities, especially the older ones, are home to aged trees that were originally planted for environmental beautification and aesthetics. However, due to the current global climate change and increased vulnerability to abiotic and biotic stressors, the old trees could pose threats to pedestrians, structures, and roads within the university campus environments. Therefore, the objective of this paper is to develop a geodatabase and evaluate the health risk assessment of avenue trees on selected roads in a tertiary institution in Ibadan, Oyo State, Nigeria using appropriate standard methods. Results obtained reported a total of 121 individual avenue trees belonging to 14 species along the study roads. The geospatial distribution analysis revealed that Emotan road had a lower density of avenue trees compared to Benue and Oduduwa roads. Furthermore, the health risk assessment indicated that 17.35% of the individual avenue trees had defects, posing potential hazards and risks of tree failure, and potential damage to pedestrians, vehicles, and neighboring utilities. The developed geodatabase is user-friendly and allows for easy data storage and quick information retrieval on the avenue trees, enhancing their maintenance and risk management. Furthermore, this study shows that systematic replacement, replanting, and management of avenue tree species could be a proactive initiative for the expansion of the geodatabase and to reduce negative health impacts.